Dissecting the Immunological Microenvironment of Glioma Based on IDH Status: Implications for Immunotherapy - Miyu Kikuchi; Hirokazu Takami; Yukari Kobayashi; Koji Nagaoka; Yosuke Kitagawa; Masashi Nomura; Shunsaku Takayanagi; Shota Tanaka; Nobuhito Saito; Kazuhiro Kakimi (Cells)
Gliomas, particularly IDH-wildtype ones, are associated with poor prognosis, yet their immunological landscape remains uncertain. We analyzed RNA sequencing data from 55 glioma patients, estimating immune infiltration with CIBERSORTx and immune cell states via Ecotyper. IDH-wildtype gliomas showed significantly higher immune cell infiltration (p = 0.002), notably of regulatory T cells (Tregs) and macrophages, and a greater proportion of exhausted T cells compared to IDH-mutant gliomas. Clustering based on immune profiles revealed two groups. Cluster A, enriched for IDH-wildtype cases, exhibited heightened immune infiltration but also marked immunosuppression. Cluster B, which included both IDH-wildtype and mutant cases, showed lower levels of immune infiltration. Tumor-infiltrating lymphocyte (TIL) cultured from IDH-wildtype tumors demonstrated limited expansion following anti-PD-1, a CSF1R inhibitor, or a STAT3 inhibitor treatment, without clear cluster-specific differences. Tumor-reactive TILs were mainly observed in cluster A. These findings highlight that IDH-wildtype gliomas have an immunosuppressive and heterogeneous microenvironment, potentially limiting responses to single-agent immunotherapies. A personalized, multi-targeted approach addressing multiple immunosuppressive mechanisms may be essential to improve immunotherapy outcomes in this aggressive glioma subgroup.